ESP32-Based Real-Time Blood Typing Detection for Emergency and Rural Use - Stephanus, Alphin; Tansiana Mbitu, Elisabeth; Gazali Suatkab, Syukri; Daus Salamoni, Thenny (Publisher Cv. Inara, 2025)
Accurate blood group identification is essential in emergency medical care, especially in rural or remote areas with limited access to laboratory facilities. This paper presents the design and development of a low-cost, real-time blood typing detection device focused on the ABO blood group system. The device utilizes an ESP32 microcontroller to process optical input signals based on agglutination reactions between blood samples and antisera. Measurement results are displayed directly on an LCD screen, providing immediate and easy-to-read feedback without the need for internet connectivity or external devices. The system is compact, portable, and user-friendly, making it ideal for use in field operations, mobile clinics, or basic healthcare units. Initial testing shows the device is capable of accurately determining blood types A, B, AB, and O in real-time, supporting rapid decision-making in critical situations.